2017
DOI: 10.1001/jama.2017.10572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Prednisolone on Symptom Duration and Severity in Nonasthmatic Adults With Acute Lower Respiratory Tract Infection

Abstract: IMPORTANCE Acute lower respiratory tract infection is common and often treated inappropriately in primary care with antibiotics. Corticosteroids are increasingly used but without sufficient evidence.OBJECTIVE To assess the effects of oral corticosteroids for acute lower respiratory tract infection in adults without asthma.DESIGN, SETTING, AND PARTICIPANTS Multicenter, placebo-controlled, randomized trial (July 2013 to final follow-up October 2014) conducted in 54 family practices in England among 401 adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The results, reported in JAMA ,1 showed no significant effect of prednisolone on the duration or severity of symptoms. The median duration of cough was five days (interquartile range 3 to 8 days) in patients given prednisolone and was also five days (3 to 10 days) in the placebo group (adjusted hazard ratio 1.11 (95% confidence interval 0.89 to 1.39); P=0.36).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The results, reported in JAMA ,1 showed no significant effect of prednisolone on the duration or severity of symptoms. The median duration of cough was five days (interquartile range 3 to 8 days) in patients given prednisolone and was also five days (3 to 10 days) in the placebo group (adjusted hazard ratio 1.11 (95% confidence interval 0.89 to 1.39); P=0.36).…”
mentioning
confidence: 84%
“…Oral corticosteroids do not reduce the severity or duration of symptoms of acute lower respiratory tract infections in adults without asthma, a randomised study has reported,1 prompting the researchers to advise against using steroids in these patients.…”
mentioning
confidence: 99%
“…For acute sinusitis, meta-analysis of RCTs has deemed systemic steroids to be ineffective as monotherapy, and the small benefit in symptom relief when used as an adjuvant therapy with antibiotics could possibly be explained by attrition bias [8]. An RCT also revealed that systemic steroids are ineffective in the treatment of lower respiratory tract infections [4]. All the prior RCTs investigating systemic steroid use in community-acquired pneumonia recruited hospitalized patients; among them, steroids as adjuvant therapy to proper antibiotics were shown to reduce mortality and morbidity only in patients with severe pneumonia but not for those with nonsevere pneumonia, casting doubt on generalizing the effectiveness to the ambulatory settings [26].…”
Section: Plos Medicinementioning
confidence: 99%
“…Using systemic corticosteroids in the treatment of acute respiratory tract infections (ARTIs) in the outpatient settings is not recommended by clinical guidelines [1][2][3]. Data from randomized control trials (RCTs) show that systemic steroids are ineffective in the treatment of lower respiratory tract infections [4]. Similar-albeit more limited-data also show the lack of effectiveness of steroid use in the common cold [5] and otitis media [6].…”
Section: Introductionmentioning
confidence: 99%
“…The collection of diary scores will not be limited to the time during which study medication is being used, to allow the capture of total symptom duration. The diary has previously been validated and is sensitive to change and internally reliable [25,26].…”
Section: Follow-upmentioning
confidence: 99%